(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article analyzes the legal aspects of the functioning of news communities of social networks. The overwhelming popularity of publics has led to violations of the rights of users to the content and personal data they host, while at the same time there is a legal vulnerability of the communities themselves. It is necessary to develop a comprehensive legal status of publics as sources of original and popular content among journalists and users of social networks. Keywords: news communities of social networks, publics, social networks, information sources, personal data, copyrights, administrator of the news community, media, journalists, users, rules of the news community, legal status of the public. DOI 10.18522/1995-0640-2020-1-208-217